2020
DOI: 10.1093/femsec/fiaa175
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community dynamics across developmental stages of fungal fruiting bodies

Abstract: Increasing evidence suggest that bacteria form diverse communities in various eukaryotic hosts, including fungi. However, little is known about their succession and the functional potential at different host development stages. Here we examined the effect of fruiting body parts and developmental stages on the structure and function of fungus-associated bacterial communities. Using high-throughput sequencing, we characterized bacterial communities and their associated potential functions in fruiting bodies from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 49 publications
7
30
0
Order By: Relevance
“…Interestingly, Planctomycetes was also abundantly found in soils but not in basidiomata belonging to the Agaricales genera: Amanita , Lactarius , Paxillus , and Russula in eastern Estonia ( 47 ). In addition, similar results have been reported in some Basidiomycetes , where the bacterial community structures differ between internal and external parts of the fruiting body but not between inner tissues ( 46 ). For fungi, our results demonstrated that (i) the Basidiomycota were dominant in soil, and the Rozellomycota tended to live in soil adhered to the truffle peridium, that is, a clear shift from Basidiomycota- to Rozellomycota-associated soils compared to truffle ascomata.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Interestingly, Planctomycetes was also abundantly found in soils but not in basidiomata belonging to the Agaricales genera: Amanita , Lactarius , Paxillus , and Russula in eastern Estonia ( 47 ). In addition, similar results have been reported in some Basidiomycetes , where the bacterial community structures differ between internal and external parts of the fruiting body but not between inner tissues ( 46 ). For fungi, our results demonstrated that (i) the Basidiomycota were dominant in soil, and the Rozellomycota tended to live in soil adhered to the truffle peridium, that is, a clear shift from Basidiomycota- to Rozellomycota-associated soils compared to truffle ascomata.…”
Section: Discussionsupporting
confidence: 84%
“…These specific conditions might be a deterministic factor of paramount ecophysiological relevance that strongly filter certain bacteria from the surrounding soils and allow them to proliferate in the truffle tissues due to the symbiotic or environmental requirements of ascomata-endophytic bacteria in ascomata ( 45 ). Physical and chemical changes include, for example, pH, temperature, oxygen levels, organic carbon availability, and ammonium released during chitin degradation in the course of fruit bodies maturation process, which may be selective factors for certain bacterial groups ( 46 , 47 ). At the same time, the soil surrounding the ascomata constitutes a reservoir of biodiversity, from which specific bacterial communities are differentially recruited both in the truffle compartments and in the ectomycorrhizosphere.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed two mature and one not yet fully developed fruiting body with FISH, and importantly, the total number of signals on the three fruiting bodies was similar, although the immature fruiting body showed a higher content of β- and γ-Proteobacteria. This indicates a development-stage-dependent shift of the bacterial composition on fruiting bodies, similar to what has previously been shown for Cantharellus cibarius (48). Our investigation of mycelial and rhizomorphic tissues of S. lacrymans with different single probes revealed individual bacterial cells but no spatial bacterial dispersal pattern (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…This indicates a development-stage-dependent shift of the bacterial composition on fruiting bodies, similar to what has previously been shown for Cantharellus cibarius(48). Our investigation of mycelial and rhizomorphic tissues of S. lacrymans with different single probes revealed individual bacterial cells but no spatial bacterial dispersal pattern (Fig.…”
supporting
confidence: 86%
“…The mature fruiting bodies (developing many basidiospores) were associated with β- and γ-Proteobacteria. This could hint at a development-dependent shift in the bacterial composition on fruiting bodies, similar to what has previously been shown for Cantharellus cibarius [ 71 ], but more targeted research is necessary to answer this question. Our investigation of the mycelial and rhizomorphic tissues of S. lacrymans with different single probes revealed individual bacterial cells but no spatial bacterial dispersal pattern ( Figure S8 ).…”
Section: Discussionmentioning
confidence: 59%